The Santa Luz chromite-peridotite and associated mafic dykes, Bahia-Brazil: remnants of a transitional-type ophiolite related to the Paleoproterozoic (>2.1 Ga) Rio Itapicuru greenstone belt? - Olivera, Elson Paiva (2007)
The Santa Luz chromite rich peridotite complex crops out in the Serrinha Block, NE Sao Francisco Craton, aproximately between grey gneisses of the Archean basament and supracrustal rocks of Palaeoproterozoic rocks of the Rio Itapicuru greenstone belt. It comprise serpentinites, serpentinized harzburgites, massive chromitites, gabbroic lenses and amphibolite dykes/veins with epidote rich margins this rocks association is interpreted as melt percolation of mantle peridotites followed by ocean floor metasomatism. Massive chromitites show major elements chemistry and platinum group elements signature similar than ophiolite chromitites.Aplites and pegmatitic dikes intrude the peridotite complex. The complex is older than 2085 Ma and younger than 2983 Ma based on U-Pb ages obtained respectively on a pegmatite dyke and a host banded gneiss. The Santa Luz peridotite complex and associated mafic dykes may have its origin related to rifting of a magma-poor continental margin that later evolved into an ocean and eventually formed the Palaeoproterozoic Rio Itapicuru Greenstone belt.